Identify the degree of socio-psychological self-assessment team - V. Avdeev; A. Lebedev (Модернизация, инновация, развитие, 2016)
The article deals with theoretical aspects of the work and organizational psychology, organizational climate survey and analysis of the employees of the State Fire squad № 211 public institutions "Fire and rescue center". The purpose of this article – definition of psychological climate in the organization. To determine the psychological climate squad used a technique A. Nemov at identifying the degree of integration "SPSK" – social and psychological self-assessment team. This methodology is designed to study the level of social and psychological development of the team, which is a basic and necessary prerequisite for the formation of an optimal social and psychological climate. In April 2015 a survey was conducted, which was attended by 30 people (26% of the total population of employees in the unit at the position of "fire"). Random sampling. The methodology included 75 statements describing the behavior of the individual and collective relations (70 claims of workers and 5 – control). Working statement distributed on seven blocks of 10 claims in each band respectively characteristics such as responsibility, teamwork, unity, contact (personal relationships), openness (in relation to newcomers and representatives of other groups), organization and knowledge. The article presents the results of the analysis, which have been formulated conclusions and guidelines.